Characterization of Staphylococcus aureus isolates from faecal samples of the Straw-Coloured Fruit Bat (Eidolon helvum) in Obafemi Awolowo University (OAU), Nigeria - Akobi, Babatunji (BioMed Central, 2012)
BACKGROUND: Bats (Chiroptera) are one of the most diverse groups of mammals which carry out important ecological and agricultural functions that are beneficial to humans. However, they are increasingly recognized as natural vectors for a number of zoonotic pathogens and favourable hosts for zoonotic infections. Large populations of the Straw-Coloured Fruit Bat (Eidolon helvum) colonize the main campus of the Obafemi Awolowo University (OAU), Ile-Ife, Nigeria, but the public health implications of faecal contamination and pollution by these flying mammals is unknown. This study characterized S. aureus obtained from faecal samples of these migratory mammals with a view to determining the clonal types of the isolates, and to investigate the possibility of these flying animals as potential reservoir for zoonotic S. aureus infections. RESULTS: One hundred and seven (107) S. aureus isolates were recovered from 560 faecal samples in eleven roosting sites from January 2008 to February 2010. A large proportion of the isolates were susceptible to antibiotics, and molecular characterization of 70 isolates showed that 65 (92.9%) were assigned in coagulase type VI, while accessory gene typing classified 69 isolates into the following: type I (12; 17.1%), type II (3; 4.3%), type III (1; 1.4%) and type IV (53; 75.7%). On the whole, the isolates were grouped in five (A-E) main genotypes. Of the ten representative isolates selected for multilocus sequence typing (MLST), nine isolates were assigned with new sequence types: ST1725, ST1726, ST1727, ST2463-ST2467 and ST2470. Phylogenetic analysis provided evidence that S. aureus isolates in group C were closely related with ST1822 and associated clones identified in African monkeys, and group D isolates with ST75, ST883 and ST1223. The two groups exhibited remarkable genetic diversity compared to the major S. aureus clade. CONCLUSIONS: Antibiotic resistance in faecal S. aureus isolates of E. helvum is low and multiple unique S. aureus lineages co-existed with E. helvum. The Straw-Coloured Fruit Bat in Ile-Ife, Nigeria is colonized predominantly by ST1725, ST1726, ST2463 and ST2470 with distinct genotypic characteristics that are rarely found in humans. This study has demonstrated on the possible existence of a reservoir of indigenous and anciently-divergent S. aureus clones among mammals in Africa.